2017
DOI: 10.3758/s13414-017-1290-0
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence in favor of prior entry from endogenous attention to a location in space

Abstract: Titchener's (1908) law of prior entry states that "the object of attention comes to consciousness more quickly than the objects which we are not attending to," or otherwise, that attended stimuli are perceived earlier than unattended stimuli. Shore, Spence, and Klein (Psychological Science, 12, 205-212. doi: 10.1111/1467-9280.00337 , 2001) showed that endogenous visuospatial orienting does in fact elicit prior-entry effects, albeit to a smaller degree than does exogenous visuospatial orienting. In disagreement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Additionally, our model provides some limited evidence that valid endogenous cues improved the fidelity with which colours were encoded. This pattern of results is consistent with the findings of Redden et al [15] and Redden et al [16], both of which found that biasing attention to one of two target locations in TOJ tasks using between-block instructions improved the probability and/or fidelity of the encoding of colour information. Building on these papers, our study provides the first evidence for the effects of endogenous spatial cueing on the probability and fidelity of colour encoding.…”
Section: Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, our model provides some limited evidence that valid endogenous cues improved the fidelity with which colours were encoded. This pattern of results is consistent with the findings of Redden et al [15] and Redden et al [16], both of which found that biasing attention to one of two target locations in TOJ tasks using between-block instructions improved the probability and/or fidelity of the encoding of colour information. Building on these papers, our study provides the first evidence for the effects of endogenous spatial cueing on the probability and fidelity of colour encoding.…”
Section: Methodssupporting
confidence: 91%
“…To date, little research has been done using the Zhang and Luck [11] colour wheel method to investigate the effects of spatial attention on conscious perception: to our knowledge, the only two attentional studies to use this analysis have been Redden et al [15] and Redden et al [16]. These two studies integrated the colour wheel into temporal order judgement (TOJ) tasks as a diagnostic to verify that attention was being biased towards the intended locations in space, and manipulated spatial attention endogenously via between-block instructions that informed participants where colour probes were more likely to appear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have pointed out that endogenous attentional changes, like the ones we were expecting after HFS, can lead to significant perceptual biases towards the attended location or modality, resulting in a prioritization of stimuli presented at the attended body site (e.g. 13 , 24 , 39 42 , 45 ). Taken together these results indicate that TOJ tasks are sensitive in detecting perceptual biases induced by exogenous and endogenous shifts in spatial attention.…”
Section: Discussionmentioning
confidence: 63%
“…Indeed, previous studies have reported a larger vertex negativity in response to sensory stimuli presented within the focus of attention 18 23 . Our hypothesis, that HFS would prompt an endogenous attentional deployment towards the stimulated arm leading to a perceptual bias, was tested by using a temporal order judgment (TOJ) task, a well-established method to assess perceptual biases 12 , 13 , 24 26 .…”
Section: Introductionmentioning
confidence: 99%